THE STUDY OF TINGKEBAN RITUAL IN ATTA HALILIN - Qori’atus Sholikhah; Dewanto (Indonesian language and literature education program Majapahit Islamic University, 2023)
Tingkeban is one of the traditions of the Javanese. This tradition has been passed down from generation to generation until now. The tingkeban ritual is carried out with the aim of being a means of praying so that the unborn baby in the womb is always given health. The Javanese still believe this tingkeban tradition must be carried out in the Javanese society, so this is as the reason the writers did research. To support the problems in this research, the writers used semiotic theory. The theory is used discussed to find the meaning in which found in tingkepan ritual. Because this research studies the meaning of each procession carried out in Aurel Hermansyah's Tingkeban ritual and the data taken comes from the video of Aurel Hermansyah's Tingkeban ritual which is uploaded to the Atta Halilintar YouTube channel. The aim of this tradition is to make the baby in the womb are protected from disaster. Keywords: tingkeban, ritual, and tradition